2015
DOI: 10.1002/glia.22873
|View full text |Cite
|
Sign up to set email alerts
|

Slow degradation in phagocytic astrocytes can be enhanced by lysosomal acidification

Abstract: Inefficient lysosomal degradation is central in the development of various brain disorders, but the underlying mechanisms and the involvement of different cell types remains elusive. We have previously shown that astrocytes effectively engulf dead cells, but then store, rather than degrade the ingested material. In the present study we identify reasons for the slow digestion and ways to accelerate degradation in primary astrocytes. Our results show that actin-rings surround the phagosomes for long periods of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 69 publications
(93 reference statements)
0
30
0
Order By: Relevance
“…A general slow digestion in astrocytes may be explained by their antigen presentation properties. Several studies have suggested that astrocytes are involved in T-cell activation because they express major histocompatibility complex class II ( Cornet et al, 2000 ; Lööv et al, 2015 ). Accordingly, T-cell infiltration has been observed in the PD brain at advanced disease stages.…”
Section: Discussionmentioning
confidence: 99%
“…A general slow digestion in astrocytes may be explained by their antigen presentation properties. Several studies have suggested that astrocytes are involved in T-cell activation because they express major histocompatibility complex class II ( Cornet et al, 2000 ; Lööv et al, 2015 ). Accordingly, T-cell infiltration has been observed in the PD brain at advanced disease stages.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Phagocytosis is mediated by both professional and non-professional phagocytic cells including macrophages, dendritic cells, tissue-infiltrating monocytes, neutrophils, and eosinophils as well as epithelial cells of mammary epithelium and astrocytes in the brain. [38][39][40] However, in the majority of cases, phagocytic clearance is primarily undertaken by macrophages. 37 This is likely the case in the context of hematopoietic engulfment of chondrocytes during fracture repair, since we show macrophages are present at the Transition Zone.…”
Section: Discussionmentioning
confidence: 99%
“…Professional phagocytes are composed of macrophages, immature dendritic cells (DCs), tissue-infiltrating monocytes, neutrophils, and eosinophils. Non-professional phagocytes in the lung consist predominantly of epithelial cells but include cells such as connective tissue cells, muscle cells and endothelial cells [101,102]. Removing cell debris and eliminating cells undergoing programmed cell death are crucial processes in containing ongoing inflammation and the resolution of inflammation [103,104].…”
Section: Phagocytosis Of Lmsmentioning
confidence: 99%